The Streptococcal Superantigen Smez Exhibits Wide Allelic Variation, Mosaic Structure, and Significant Antigenic Variation - Proft, Thomas (The Rockefeller University Press, 2000)
The frequencies of the newly identified streptococcal superantigen genes smez, spe-g, and spe-h were determined in a panel of 103 clinical isolates collected between 1976 and 1998 at various locations throughout New Zealand. smez and spe-g were found in every group A Streptococcus (GAS) isolate, suggesting a chromosomal location. The spe-h gene was found in only 24% of the GAS isolates and is probably located on a mobile DNA element. The smez gene displays extensive allelic variation and appears to be in linkage equilibrium with the M/emm type. 22 novel smez alleles were identified from 21 different M/emm types in addition to the already reported alleles smez and smez-2 with sequence identities between 94.5 and 99.9%. Three alleles are nonfunctional due to a single base pair deletion. The remaining 21 alleles encode distinct SMEZ variants. The mosaic structure of the smez gene suggests that this polymorphism has arisen from homologous recombination events rather than random point mutation. The recently resolved SMEZ-2 crystal structure shows that the polymorphic residues are mainly surface exposed and scattered over the entire protein. The allelic variation did not affect either Vβ specificity or potency, but did result in significant antigenic differences. Neutralizing antibody responses of individual human sera against different SMEZ variants varied significantly. 98% of sera completely neutralized SMEZ-1, but only 85% neutralized SMEZ-2, a very potent variant that has not yet been found in any New Zealand isolate. SMEZ-specific Vβ8 activity was found in culture supernatants of 66% of the GAS isolates, indicating a potential base for the development of a SMEZ targeting vaccine.